2017
DOI: 10.1152/ajpendo.00356.2016
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein effects on energy balance link the intestinal mechanisms of energy absorption with adiposity and hypothalamic neuropeptide gene expression

Abstract: .2016.-We tested the hypothesis that dietary whey protein isolate (WPI) affects the intestinal mechanisms related to energy absorption and that the resulting energy deficit is compensated by changes in energy balance to support growth. C57BL/6 mice were provided a diet enriched with WPI with varied sucrose content, and the impact on energy balance-related parameters was investigated. As part of a high-sucrose diet, WPI reduced the hypothalamic expression of pro-opiomelanocortin gene expression and increased en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 52 publications
7
42
0
Order By: Relevance
“…Cumulative energy intake, one-way ANOVA: F (2,22) =81·7 ( P <0·001 followed by Bonferroni's post hoc test). Hypothalamic gene expression, one-way ANOVA: pomc F (2,22) =9·2 ( P <0·01); npy F (2,22) =2·8 ( P =0·079); ghsR F (2,22) =9·8 ( P <0·01); all followed by Bonferroni's post hoc test except npy . (a, b) , LFD-CAS; , HFD-CAS; , HFD-LAB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cumulative energy intake, one-way ANOVA: F (2,22) =81·7 ( P <0·001 followed by Bonferroni's post hoc test). Hypothalamic gene expression, one-way ANOVA: pomc F (2,22) =9·2 ( P <0·01); npy F (2,22) =2·8 ( P =0·079); ghsR F (2,22) =9·8 ( P <0·01); all followed by Bonferroni's post hoc test except npy . (a, b) , LFD-CAS; , HFD-CAS; , HFD-LAB.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we showed that WPI reduced epididymal white adipose tissue (eWAT) weight and the overall body weight gain. Consistent with changes in the gut, WPI increased energy intake, which was reflected in the altered hypothalamic gene expression of neuropeptides, namely, proopiomelanocortin ( pomc ), neuropeptide Y ( npy ) and ghrelin ( 22 ) .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Among different sources of proteins, whey proteins seem to be the most effective [4]. Several mechanisms have been invoked to explain the appetite-suppressant and weight-losing effects that whey proteins produce when administered to normal weight or obese subjects [5]: secretion of gastrointestinal anorexigenic peptides [6][7][8][9], stimulation of energy expenditure via an increased thermogenesis [10], and direct actions on specific hypothalamic areas involved in the regulation of food intake [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to nesfatin-1, ghrelin as an orexigenic peptide increase food intake behavior during energy deficiencies status/negative energy balance situations (starvation, fasting, cachexia, malnutrition, weight reduction, calorie restriction, eating disorders) [32][33][34]. In addition, to energy regulation matter, it has been shown that different nutrients manipulation has also impact on ghrelin levels and gene expression [35,36]. A varieties of actions for ghrelin on different bodily system, energy regulation, metabolic functions, regulatory action on some appetite peptides, and some other function have been mentioned [26,37].…”
Section: Aerobic Exercise and Herb Supplementation Increase Liver Andmentioning
confidence: 99%